Glutamate released in the preoptic area during sexual behavior controls local estrogen synthesis in male quail - de Bournonville, Catherine (Psychoneuroendocrinology, 2017)
Estrogens are known to act rapidly, probably via membrane estrogen receptors, to induce fast effects on physiological and behavioral processes. Engaging in some of these behaviors, such as sexual behavior, results in an acute modulation of the production of estrogens in the brain by regulating the efficiency of the estrogen synthase enzyme, aromatase. Specifically, we recently demonstrated that aromatase activity (AA) in the male quail brain is rapidly inhibited in discrete brain regions including the medial preoptic nucleus (POM) following exposure to a female. Evidence from in vitro studies point to glutamate release as one of the mechanisms controlling these rapid regulations of the aromatase enzyme. Here, we show that (a) the acute injection of the glutamatergic agonist kainate into the POM of anesthetized male quail inhibits AA and (b) glutamate is released in the POM during copulation. These results provide the first set of in vivo data demonstrating a role for glutamate release in the rapid control of AA in the context of sexual behavior.